Maternal Regulation of Daughters' Emotion During Conflicts From Early to Mid‐Adolescence. (8th July 2015) - Lougheed, Jessica P.; Hollenstein, Tom; Lewis, Marc D.
Abstract : Primary caregivers play an important role in emotion socialization. Real‐time mother–daughter emotion socialization was examined in 45 mother–daughter dyads with early‐adolescent daughters (age M = 11.80, SD = .27) at the first observation point. Maternal supportive emotion regulation and daughters' emotions were coded during two conflict discussions, 2 years apart. With multilevel survival analysis, the likelihood of maternal supportiveness was predicted both over time, between early and mid‐adolescence, and by daughters' pubertal status. Mothers were more likely to respond to daughters' negative and positive emotions with supportiveness for daughters whose pubertal maturation occurred relatively early. Results suggest that mothers adjust their socialization of daughters' emotions according to their daughters' pubertal development.